"Three-education" Synergistic Innovation Driven by New Quality Productive Forces: Connotation Deconstruction, Logical Deduction (Asian Journal of Social Science Studies, 2024)
The new quality productive forces led by science and technology innovation is reshaping the global economic and social structure, with far-reaching impacts on the field of education. In this context, "three-education" collaborative innovation has become a key force to promote the modernization of education. The new quality productive forces will optimize the allocation of educational resources through scientific and technological means, promote the transformation of the education model and conceptual innovation, and lead the education system to deep-level changes. In this change, technological innovation and educational innovation are mutually empowering, emphasizing the core role of interdisciplinary integration and open cooperation in building a new era of educational ecology. To cope with this trend, the "three educators" collaborative innovation should build a smart education platform, implement cross-border integration education strategies, establish an ecosystem for industry-education integration, build an open resource symbiosis network, and innovate the education evaluation system. These strategies are aimed at cultivating high-quality talents that meet the needs of the new era and providing solid human and intellectual support for high-quality economic and social development.